2016
DOI: 10.1007/s00221-016-4675-8
|View full text |Cite
|
Sign up to set email alerts
|

Postural sway in men and women during nauseogenic motion of the illuminated environment

Abstract: We exposed standing men and women to motion relative to the illuminated environment in a moving room. During room motion, we measured the kinematics of standing body sway. Participants were instructed to discontinue immediately if they experienced any symptoms of motion sickness, however mild. For this reason, our analysis of body sway included only movement before the onset of motion sickness. We analyzed the spatial magnitude of postural sway in terms of the positional variability and mean velocity of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…Hence, what would have upset task performance became a resource for exploring the task space for the eventuality of a major loss of sensory information. And now, we see that a less multifractal postural system can be more stable (e.g., smaller t MF in [42]; and smaller W MF in [38,39]) and, as present findings indicate, more accurate in how it orients behaviors to a visually-guided aiming task.…”
Section: The Value Of Multifractal Fluctuation Is Specific To Task Cosupporting
confidence: 71%
“…Hence, what would have upset task performance became a resource for exploring the task space for the eventuality of a major loss of sensory information. And now, we see that a less multifractal postural system can be more stable (e.g., smaller t MF in [42]; and smaller W MF in [38,39]) and, as present findings indicate, more accurate in how it orients behaviors to a visually-guided aiming task.…”
Section: The Value Of Multifractal Fluctuation Is Specific To Task Cosupporting
confidence: 71%
“…Note that in our study there were few females compared to males. From past research, it is known that females are generally more prone to sickness (e.g., Koslucher, Munafo, & Stoffregen, 2016), therefore gender could be an issue in the interpretation of our results. However, in future work, we want to consider having a navigation system with close-loop feedback, namely looping real-time behavioral measurements with navigation control laws so that the navigation system automatically adapts to the level of sickness of the user.…”
Section: Discussionmentioning
confidence: 87%
“…Palatinus et al [33] found that the multifratality of torso movement varied as a function of “perceptual intent”, that is, whether participants were attempting to detect the whole length or the partial length of an unseen rod that was attached to their shoulders. Finally, Koslucher et al [53] found, in young adults, that the multifractality of standing body sway differed between participants who proved to be susceptible to visually induced motion sickness and those who did not become sick. Much additional research will be required to identify reliable links between patterns of multifracality in human movement and particular states, situations, conditions, or diagnoses of the individuals involved.…”
Section: Discussionmentioning
confidence: 99%